Intergration of vision based road lane detection for automatic streeting control (ASC) application - Dwijotomo, Abdurahman (2015)
Technology over vision based road lane detection for vehicle navigation have been developed in recent years due to increasing interest in the Inteligent Transportation System (ITS). However, most of the vision systems are still in development stage and continous researchs are required to improve the accuracy of the system. This study sought the possibilities of developing Automatic Steering Control (ASC) when the vision system is integrated into the vehicle control. The ASC development provide solution to solve communication interface between vision system and vehicle steering seamlessly. The outcome in this study is the demonstration of ASC system which is capable of assisting the navigation of the vehicle and follow the road with less human interruption. To achieve this, vision system which proccess road direction for navigation are used as vehicle steering system input. The vision system consist of camera and computer, meanwhile steering system are built based from Steer By Wire (SBW) design to add capabilities of electronic control inside vehicle. SBW use electromechanical actuator to drive the steering and with electronic controller to control movement. Thus, communication of vision system input to steering system become possible by utilizing electronic data. Experimental validations were performed to demonstrate ASC system based on vision road lane detection. The result shows this system is capable to run on road within a speed limit of 30 km/h and visibility of more than 1 km. Other researchers have work with the use of different type of sensors (combination of GPS and Lidar- Light Radar) and proven to achieve 40 km/h speed limit with no visibility limitation as demonstrated in DARPA (Defense Advance Research Project Agency) Grand Challenge (DARPA, 2005). It can be concluded that ASC system with vision based lane detection have been successfully demonstrated with some limitations.